Pengaruh Tes Formatif Pilihan Ganda dan Gaya Berpikir Siswa terhadap Hasil Kuis Statistika - Diana S. Mandar (Universitas Bunda Mulia, 2017)
The importance of the application of statistics, it is expected students to master these basic subjects. Because in addition as a means of scientific thinking that is needed by the students, to develop the capacity to think. It required range of tests based on issues that are very effective approach to test these capabilities. The results of this study is expected to show that thinking styles have an influence on students 'quiz results statistics that depend on various tests, after reducing the linear influence students' attitudes toward statistics.Keywords: Statistic, Design of Experiment (DOE), Learning Process